Determinants of contraceptive use among sexually active unmarried adolescent girls and young women aged 15–24 years in Ghana: a nationally representative cross-sectional study - Felix Boakye Oppong; Divine Darlington Logo; Senyo Yao Agbedra; Anthony Agyapong Adomah; Seidu Amenyaglo; Kingsley Arhin-Wiredu; Samuel Afari-Asiedu; Kenneth Ayuurebobi Ae-Ngibise (BMJ Open)
Objective There is a decline in contraceptive use among sexually active unmarried young women in Ghana. This study assessed the prevalence of contraceptive knowledge and use, and the determinant of contraceptive use among sexually active unmarried young women in Ghana.Design This was a nationally representative cross-sectional survey, using data from the 2017 Ghana Maternal Health Survey. Weighted logistic regression was used to assess the association between background and obstetric characteristics of young women and contraceptive use.Setting Ghana.Participants A total of 809 sexually active unmarried adolescent girls (15–19 years) and young women (20–24 years).Primary and secondary outcome measures Knowledge and use of both modern and traditional contraceptive methods.Results Knowledge of at least one modern and traditional contractive method was 99.8% and 95.0%, respectively. The prevalence of contraceptive use was 43%—with 34% modern and 9% traditional methods. From the unadjusted analyses, age (p=0.002), past pregnancy (p<0.001), abortion in the past 5 years (p=0.007) and history of childbirth (p=0.025) were independently associated with contraceptive use, whereas education (p=0.072), place of residence (p=0.702), household wealth (p=0.836) and age at first sex (p=0.924) were not independently associated with contraceptive use. In the adjusted analysis, contraceptive use was significantly higher among respondents with secondary education compared with those with primary education (OR 2.43, 95% CI 1.31 to 4.49, p=0.017), and was higher among respondents with a history of pregnancy (OR 2.13, 95% CI 1.48 to 3.06, p<0.001).Conclusion There is a significant gap between knowledge and use of contraceptives among the study population. While intensifying knowledge of adolescents and young women on contraceptives, adolescent-friendly corners should be established at vantage points to increase utilisation and to prevent societal stigma on young women who access contraceptives services.